2013
DOI: 10.1371/journal.pone.0055786
|View full text |Cite
|
Sign up to set email alerts
|

Class II HDAC Inhibition Hampers Hepatic Stellate Cell Activation by Induction of MicroRNA-29

Abstract: BackgroundThe conversion of a quiescent vitamin A storing hepatic stellate cell (HSC) to a matrix producing, contractile myofibroblast-like activated HSC is a key event in the onset of liver disease following injury of any aetiology. Previous studies have shown that class I histone deacetylases (HDACs) are involved in the phenotypical changes occurring during stellate cell activation in liver and pancreas.AimsIn the current study we investigate the role of class II HDACs during HSC activation.MethodsWe charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 57 publications
3
62
0
3
Order By: Relevance
“…In patients with ALS, the upregulation of HDAC4 in skeletal muscle is associated with muscle denervation [35]. Additionally, HDAC4 has been related to fibrosis [36]; Barbier-Torres et al [37] showed that HDAC4 expression promoted cholestatic liver injury and alleviated liver fibrosis in mice. Interestingly, PDGF signaling is also overactivated in fibrotic disease [38], and its inhibition attenuates experimental liver fibrogenesis [39].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ALS, the upregulation of HDAC4 in skeletal muscle is associated with muscle denervation [35]. Additionally, HDAC4 has been related to fibrosis [36]; Barbier-Torres et al [37] showed that HDAC4 expression promoted cholestatic liver injury and alleviated liver fibrosis in mice. Interestingly, PDGF signaling is also overactivated in fibrotic disease [38], and its inhibition attenuates experimental liver fibrogenesis [39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Class I HDACs such as HDAC1 and HDAC2 were easily detected in quiescent HSCs, their protein expression decreased during stellate cell activation, whereas HDAC8 is induced and HDAC3 seems to be expressed at constant levels [29]. Among Class II HDACs, HDAC4 was accumulated during HSCs trans-differentiation, however a significant down-regulation for HDAC9, 10 and constant expressions of HDAC5, 6 and 7 were observed [9,28].…”
Section: The Expression and Functional Roles Of Hdacsmentioning
confidence: 99%
“…Yet, more research is needed to draw an accurate, global picture of the functional roles for all HDAC isoforms in liver fibrosis. Inge Mannaerts and the co-workers indicated that inhibition of Class II HDACs leads to a noticeable reduction of HSC activation markers as well as an inhibition of cell proliferation [9]. Specifically speaking, knock down experiments shows that inhibiting HDAC4, 5 and 6 partially hinders HSC activation through induction of microRNA-29, a well-known anti-fibrotic micro RNA [9].…”
Section: The Expression and Functional Roles Of Hdacsmentioning
confidence: 99%
“…In further support of a role for class II HDACs in liver fibrosis, HDAC7 and HDAC4 have been found to aid HSC activation by directly repressing HGF and MMP genes, respectively (Pannem et al , 2014, Qin andHan, 2010). Of great interest, a specific class II HDAC inhibitor MC1568 was found to significantly down-regulate fibrogenic genes in cultured HSCs and ameliorate liver fibrosis in mice (Mannaerts, Eysackers, 2013).…”
Section: Page 13 Of 24mentioning
confidence: 98%
“…Mannaerts et al conducted an expression profiling of class II HDACs in primary HSCs (Mannaerts et al , 2013). Although all known class II HDACs were expressed in HSCs, only HDAC6 and HDAC10 exhibited significant alterations during HSC activation.…”
Section: Page 13 Of 24mentioning
confidence: 99%